Strategi Pemanfaatan Gofood untuk Ekspansi UMKM Selama Pandemi Covid-19 di Banyu Urip Kidul, Surabaya - Adi Prasetyo, Djoko; Devalia Nifatul Imamah, Irfananda; Adi Firmansyah, Gilang (Jurnal Etnik: Ekonomi-Teknik, 2022)
The world is facing the Coronavirus Disease of 2019 (Covid-19) pandemic which has major implications for all sectors, namely education, economy, health and socio-politics. The government's effort to suppress the surge in Covid-19 infections and death rates in Indonesia is by implementing the Level 4 and 3 Community Activity Restrictions (PPKM) for the Java and Bali regions. These restrictions make it difficult for Indonesia to realize the 8th Sustainable Development Goals (SDG), namely decent work and economic growth, especially for the people of Banyu Urip Kidul. This is because these restrictions have an impact on Micro, Small and Medium Enterprises (MSMEs) in the food sector in Banyu Urip Kidul who do not use online media, one of which is GoFood. The method used in this community service is carried out based on the analysis of the results of observations and discussions with community members who live in Banyu Urip Kidul, Surabaya, East Java. Thus, the activity in the form of counseling about the use of GoFood media as a strategy for managing MSMEs during the pandemic was carried out with the aim that residents could expand their culinary businesses through GoFood. Meanwhile, this knowledge is new for residents so that residents are enthusiastic when participating in the counseling as evidenced by the various questions asked.